Correction: nBu4NI-Mediated oxidation of methyl ketones to α-ketoamides: using ammonium, primary and secondary amine-salt as an amine moiety. Issue 23 (26th May 2017) - Wang, Dan; Zhang, Kuan; Jia, Luhan; Zhang, Danting; Zhang, Yue; Cheng, Yujia; Lin, Chang; Wang, Bo
Abstract : Correction for ' n Bu4 NI-Mediated oxidation of methyl ketones to α-ketoamides: using ammonium, primary and secondary amine-salt as an amine moiety' by Dan Wang et al., Org. Biomol. Chem., 2017, 15, 3427–3434.